What constitutes effective learning? an introduction to Talaqqi framework - Omar, Muhd Khaizer; Md. Yunus, Aida Suraya; Ismail, Ismi Arif; Mohd Sharef, Nurfadhlina; Azmi Murad, Masrah Azrifah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
This article intends to inform people on understanding the process of learning via Talaqqi approach and how Talaqqi framework plays a role in ensuring learning transpired. Certainly, our thinking and approach to effective learning have been influenced by the concept of Talaqqi presented in this article. We listed five pillars in constructing effective learning which in our opinion, produces a significant impact in achieving meaningful learning. The elaboration of each pillar is stated in the article along with eminent contributions which briefly explained. Based on the stated pillars, we believe and drive into a conclusion as what we disclose as effective learning. Ultimately, we highlight the issue of modern education which seems to overlook on the fundamental rule of teaching due to technological advancement in education, often resulting in the haphazard of the educational milieu and oversee the primal purpose of education. The Talaqqi framework will bring back the purpose of education and inform the fundamental approach in the teaching arena although the teaching and learning have been rapidly customized to different methods, for instance online and distance learning.